A retrospective real-world observational pilot analysis of Waya: a self-monitoring fitness app in Germany. Issue 3 (10th June 2022) - Balakrishnan, Preetha; Owen, Elizabeth; Eberl, Markus; Friedrich, Benjamin; Etter, Tobias
Abstract : Background: The increasing prevalence of lifestyle-driven metabolic disorders poses a heavy burden on the healthcare system. Several low-cost, easily accessible, and effective weight loss interventions are being developed to improve this situation. Waya is one such German digital application that guides users to reach their desired weight in a healthy manner, by monitoring their eating habits and physical activity levels. In this retrospective real-world observational pilot study, we aimed to identify if the use of Waya helps in reducing weight as intended and the underlying factors associated with it. Methods: Data from healthy overweight or obese participants who provided their weight information and answered the short form of the Weight Efficacy Lifestyle Questionnaire and the International Physical Activity Questionnaire activity questionnaires once before the completion of the first module (baseline) were compared with data provided after the beginning of the last module. Age and sex-based distribution were studied and the correlation between nutrition, physical activity, and weight was analyzed. Results: Waya participants showed an improvement in nutritional behavior, physical activity levels, and weight reduction compared with baseline. These changes were independent of age and sex. Weight loss mainly correlated with improvements in nutritional behavior but not physical activity. Conclusion: The results from our pilot study showed that Waya is beneficial in bringing about short-term weight loss mainly through behavioral changes in nutrition. Although physical activity levels improved, its influence on weight loss was not apparent.